A New Thermodynamics - Mayhew, Kent W. (IJRDO-Journal of Applied Science, 2016)
Accepting that expanding systems must upwardly displace Earth’s atmosphere’s weight, and thatthis signifies lost work, renders most useful processes irreversible. This simple realization has notbeen properly addressed in thermodynamics, allowing ill-conceived second law basedexplanations to prevail. We will discuss how this mistake originates with Clausius’ theorem, andcontinues with Boltzmann’s entropy. We will discuss why we can never extract systems as muchwork from a system as the thermal energy that we put in. Then we will discuss why the traditionaltreatment of partial differentials remains so troublesome, and then provide a simpler understandingof free energies, which will lend itself to a better possible interpretation of entropy, one thatremoves our reliance on the second law. Ultimately, thermodynamics could be a simpleconstructive science. Our new interpretations may also have ramifications to our consideration ofglobal warming.